The genus Synergus Hartig (Hymenoptera: Cynipidae: Synergini) in the New World: a complete taxonomic revision with a key to species - Lobato-Vila, Irene; Pujade-Villar, Juli (Zootaxa, 2021)
A complete revision of the genus Synergus Hartig (Hymenoptera: Cynipidae: Synergini) in the New World (Nearctic and Neotropical regions) is conducted for the first time in order to stabilize its taxonomy. A total of 11 new species are described from Mexico: S. ashmeadi Lobato-Vila & Pujade-Villar, sp. nov.; S. beutenmulleri Lobato-Vila & Pujade-Villar, sp. nov.; S. compressus Lobato-Vila & Pujade-Villar, sp. nov.; S. diversicolor Lobato-Vila & Pujade-Villar, sp. nov.; S. ebenus Lobato-Vila & Pujade-Villar, sp. nov.; S. linnei Lobato-Vila & Pujade-Villar, sp. nov.; S. macrackenae Lobato-Vila & Pujade-Villar, sp. nov.; S. oaxaquensis Lobato-Vila & Pujade-Villar, sp. nov.; S. personatus Lobato-Vila & Pujade-Villar, sp. nov.; S. ruficephalus Lobato-Vila & Pujade-Villar, sp. nov.; and S. weldi Lobato-Vila & Pujade-Villar, sp. nov. Synergus splendidus Fullaway, 1911 is proposed as a syn. nov. of S. dorsalis (Provacher, 1889); S. garryana Gillette, 1893 and S. oneratus coloradensis Gillette, 1896 as syn. nov. of S. oneratus (Harris, 1841); and S. magnificus Weld, 1957 as a syn. nov. of S. reniformis McCracken & Egbert, 1922. Redescriptions and illustrations are provided for poorly characterized species. A key to species and a summary table including all valid Synergus from the New World, their biology and distribution, are given. Distribution, morphology, and trophic associations are discussed and compared between New World and Palaearctic species.